2020
DOI: 10.3390/atmos11090932
|View full text |Cite
|
Sign up to set email alerts
|

Last Deglaciation—Holocene Australian-Indonesian Monsoon Rainfall Changes Off Southwest Sumba, Indonesia

Abstract: Previous studies suggested the multi-millennial scale changes of Australian-Indonesian monsoon (AIM) rainfall, but little is known about their mechanism. Here, AIM rainfall changes since the Last Deglaciation (~18 ka BP) are inferred from geochemical elemental ratios (terrigenous input) and palynological proxies (pollen and spores). Pollen and spores indicate drier Last Deglaciation (before ~11 ka BP) and wetter Holocene climates (after ~11 ka BP). Terrigenous input proxies infer three drier periods (i.e., bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Samples were subdivided into a number of splits using a standard splitter, and ∼300 specimens were picked and counted [29], [30]. The petrographic analysis describes the texture (grain size, sorting, and contacts), sedimentary structures (laminations, bioturbation), and framework grain composition.…”
Section: Nomentioning
confidence: 99%
“…Samples were subdivided into a number of splits using a standard splitter, and ∼300 specimens were picked and counted [29], [30]. The petrographic analysis describes the texture (grain size, sorting, and contacts), sedimentary structures (laminations, bioturbation), and framework grain composition.…”
Section: Nomentioning
confidence: 99%
“…Several downcore studies have been carried out in the Indonesian waters (Figure 1), which is that, MD98-2162 (Visser et al, 2003), MD98-2170 (Stott et al, 2004), MD98-2165 (Levi et al, 2007), MD01-2378 (Xu et al, 2008), MD01-2390 (Steinke et al, 2008), SO139-74 KL (Lückge et al, 2009), GeoB 10038-4, GeoB 10029-4 (Mohtadi et al, 2010), 13GGC (Linsley et al, 2010), SHI9034 (Ding et al, 2013), MD10-3339 (Gustiantini et al, 2015), GEOB10043-3 (Setiawan et al, 2015), SO184-10043 (Li et al, 2016), BS-36 (Zuraida et al, 2017), BS-24 (Li et al, 2018), ST-13 (Damanik et al, 2019), STA3 (Hendrizan et al, 2019), OS-07 (Damanik et al, 2020a, b), and ST-08 (Ardi et al, 2019(Ardi et al, , 2020. However, only a few studies have identified the abundance and diversity of vertical planktonic foraminifera distribution to determine the marine ecological conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Gustiantini et al, 2015;Ardi et al, 2019;Hendrizan et al, 2019;Damanik et al, 2019;Damanik et al, 2020b;Ardi et al, 2020). A downcore study have also been conducted in Simeulue sub-basin, such as Li et al (2018) who reconstructed the spatiotemporal pattern of sea surface temperature (SST) (Visser et al, 2003), MD98-2170 (Stott et al, 2004), MD98-2165 (Levi et al, 2007) ), MD01-2378 (Xu et al, 2008), MD01-2390 (Steinke et al, 2008), SO139-74 KL (Lückge et al, 2009), GeoB 10038-4, GeoB 10029-4 (Mohtadi et al, 2010), 13GGC (Linsley et al, 2010), SHI9034 (Ding et al, 2013), MD10-3339 (Gustiantini et al, 2015), GEOB10043-3 (Setiawan et al, 2015) , SO184-10043 (Li et al, 2016), BS-36 (Zuraida et al, 2017), BS-24 (Li et al, 2018), ST-13 (Damanik et al, 2019), STA3 (Hendrizan et al, 2019), OS-07 (Damanik et al, 2020a, b), and ST-08 (Ardi et al, 2019(Ardi et al, , 2020. Sediment location of Core EW17-09 (red star) (modified from Lückge et al, 2009;Mohtadi et al, 2010;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations